PENGURANGAN NON VALUE ADDED ACTIVITIES MENGGUNAKAN METODE LEAN SIX SIGMA - Elly Wuryaningtyas Yunitasari (Jurnal Ilmiah Dinamika Teknik, 2018)
The purpose of this study is to improve the performance. Specific target of this research is to eliminate waste that occurs in the process while increasing the capability in the process. The method used in this study is Lean Six Sigma.Lean Six Sigma is a combination of Lean and Six Sigma can be defined as business philosophy, systematic and systematic approach to identify and eliminate waste or non value-added activities (non-value added activities) through continuous improvement to achieve six sigma performance levels, by delivering products (materials, work in process, output) from internal and external customers to pursue excellence and excellence in the form of producing only 3.4 defects for every one million occasions or operations (3 , 4 DPMO). (Gasperz.2006, pp 1-2). Integration between Lean and Six Sigma will improve performance through increased speed and accuracy (zero defect). The Lean approach will show non value added (NVA) and value added (VA) and create value added flows smoothly along the value stream process, while Six Sigma will reduce the variation of value added. (Gasperz.2006, p. 9). The formulation of the problem to be discussed in this research is to identify non value added activities and waste. The research in doing this research is to calculate Value Add and Non Value Add data, calculate Process Cycle Time (PCE) Sigma Level, identifies and calculates the waste and determines the causes of the occurrence of waste processes using the Fish Bone Diagram, performing an analysis with the FMEA method. Improved total lead time from 710 minutes, after repair to 681 minutes.Approved increase of 29 minutes. Efficiency value before improvement is 60.56% then after the improvement up to 58.88%. Keywords: Lean Six Sigma, non value added (NVA), value added (VA) and waste.